Lactate Formation in Primary and Metastatic Colon Cancer Cells at Hypoxia and Normoxia. (16th August 2016) - Graboń, Wojciech; Otto‐Ślusarczyk, Dagmara; Chrzanowska, Alicja; Mielczarek‐Puta, Magdalena; Joniec‐Maciejak, Ilona; Słabik, Krzysztof; Barańczyk‐Kuźma, Anna
Abstract : High glucose consumption and lactate synthesis in aerobic glycolysis are a hallmark of cancer cells. They can form lactate also in glutaminolysis, but it is not clear how oxygen availability affects this process. We studied lactate synthesis at various oxygen levels in human primary (SW480) and metastatic (SW620) colon cancer cells cultured with L‐Ser and/or L‐Asp. Glucose and lactate levels were determined colorimetrically, amino acids by HPLC, expression of AST1 ‐mRNA and AST2‐ mRNA by RT‐PCR. In both lines glucose consumption and lactate synthesis were higher at 10% than at 1% oxygen, and lactate/glucose ratio was increased above 2.0 by L‐Asp. AST1 ‐mRNA expression was independent on oxygen and cell line, but AST2‐ mRNA was lower at hypoxia in SW480. We conclude that, in both cell lines at 1% hypoxia, lactate is formed mainly from glucose but at 10% normoxia also from L‐Asp. At 10% normoxia, lactate synthesis is more pronounced in primary than metastatic colon cancer cells.